Perancangan Interior Pusat Informasi Kebudayaan Suku Arfak di Manokwari, Papua Barat - Jennifer Winarto; Hedy Constancia Indrani (Intra, 2017)
Art is an aspect that cannot be separated from human life. At present, however, the development of art in Surabaya is truly insignificant such that the public interest in art tends to be low, especially in visual art. Drawing from this condition and seeing how products and activities of visual arts lack accommodation in terms of spatial design, this thesis aims to design a facility that can fulfill those needs, encompassing the functions of exhibition, education, recreation, and information.In the design process, the problems of this project are how to design the interior of a visual art center that not only accommodate the needs of the arts in Surabaya, but also attract visitors in accordance with the lifestyle of the metropolitan youth nowadays.The method used in this design follows the Zeisel diagram with additional adjustments of the drafting process, which explains a design process that rotates from the end result and can be returned to the initial stages of design to be fixed in order to achieve the most optimal results. Six of these methods include basic e-b knowledge (preliminary stages of data collection), programming research (programming phase), design and design review (transformation stage design), construction (design development stage), use + adaptation (the final design stage), and evaluation research (evaluation phase).The final design applies a ‘recreational’ concept, that seeks to accommodate the needs of visual art products and activities in Surabaya by providing facilities for education, information, exhibitions, and recreation such as exhibition area, library, lecture theater and studio, as well as supporting spaces such as cafes and offices. The design efforts to improve visitor’s interests in accordance with the lifestyle and culture of the people are applied through the ‘recreational’ concept, namely by providing spaces that bring novel experiences and improve the quality of those experiences.